Особливості вікових стадій Cymbochasma borysthenica (Pall. ex Schlecht.) Klokov et Zoz (Orobanchaceae) - Кучеревський, В.В.; Баранець, М.О.; Сіренко, Т.В. (Український ботанічний журнал, 2013)
Приведены результаты исследований большого жизненного цикла Cymbochasma borysthenica. Акцентируется внимание на особенностях прохождения возрастных состояний особей семенного и вегетативного происхождения и клона (кондивидуума) в целом. Results of the study of the greater life cycle of Cymbochasma borysthenica are presented. The attention was focused on peculiarities of the age stages of individuals of the seed and vegetative origin, and of the clone (condividuum) as a whole.